Selected functional solutions of strategic controlling in organisations operating in Poland - Bieńkowska Agnieszka; Kral Zygmunt; Zabłocka-Kluczka Anna (Management, 2018)
Selected functional solutions of strategic controlling in organisations operating in Poland The purpose of the article is to present partial results of the nationwide research with regard to selected functional solutions of strategic controlling. They concern the concept and tasks of this controlling. The paper characterises theoretical aspects of the aforementioned issues as the basis for the interpretation of the obtained results. It presents the research methodology. It presents the obtained research results both in the general perspective, as well as with respect to detailed criteria, namely the organisation’s size and the type of environment. On the other hand, with respect to strategic controlling tasks, they were also presented with consideration of controllers and managers in the implementation of these tasks. The obtained research results are primarily practical. They may indicate to the managers in organisations the scope and manner of improvement in the functional solutions of strategic controlling. They may also suggest to the management theoreticians the need for and the directions of improvement of this type of solutions.